Pharmacokinetic and pharmacodynamic evaluation of linagliptin in African American patients with type 2 diabetes mellitus. (20th August 2013) - Friedrich, Christian; Glund, Stephan; Lionetti, Dominick; Kissling, C. James; Righetti, Julian; Patel, Sanjay; Graefe‐Mody, Ulrike; Retlich, Silke; Woerle, Hans‐Juergen
<x xml:space="preserve">Abstract</x> Aim This was an open label, multicentre phase I trial to study the pharmacokinetics and pharmacodynamics of the dipeptidyl peptidase‐4 (DPP‐4) inhibitor linagliptin in African American patients with type 2 diabetes mellitus (T2DM). Methods Forty‐one African American patients with T2DM were included in this study. Patients were admitted to a study clinic and administered 5 mg linagliptin once daily for 7 days, followed by 7 days of outpatient evaluation. Results Primary endpoints were area under the plasma concentration–time curve (AUC), maximum plasma concentration (Cmax) and plasma DPP‐4 trough inhibition at steady‐state. Linagliptin geometric mean AUC was 194 nmol l−1 h (geometric coefficient of variation, 26%), with a Cmax of 16.4 nmol l−1 (41%). Urinary excretion was low (0.5% and 4.4% of the dose excreted over 24 h, days 1 and 7). The geometric mean DPP‐4 inhibition at steady‐state was 84.2% at trough and 91.9% at maximum. The exposure range and overall pharmacokinetic/pharmacodynamic profile of linagliptin in this study of African Americans with T2DM was comparable with that in other populations. Laboratory data, vital signs and physical examinations did not show any relevant findings. No safety concerns were identified. Conclusions The results of this study in African American patients with T2DM support the use of the standard 5 mg dose recommended in all populations.